Social Skill and Self-Advocacy Goals: An IEP Study - Smith, Gregory W.; Lowrey, K. Alisa; Walker, David (Journal of the American Academy of Special Education Professionals, 2019)
The purpose of this study was to determine if self-advocacy and social skills were targeted areas of instruction on a collected sample of Individualized Education Programs (IEPs). We also measured student attendance at IEP meetings as a potential step towards self-avocation. Utilizing secondary analysis with data collected from 170 IEPs, we examined IEPs for the inclusion of social skill and self-advocacy goals as well as student attendance at the IEP. Findings indicated that while social skills and self-advocacy goals were included, many of those goals were of poor quality in target and measurability. Student attendance at the IEP was documented at an extraordinarily high rate for this sample. Discussion of these items as well as their implication for future practice is included.